Effect of Particle Size and Addition of Coconut Cell on the Quality of Sengon Wood Pellet - Anindya Husnul Hasna; J. P. Gentur Sutapa; Denny Irawati (Jurnal Ilmu Kehutanan)
The waste of sengon (Falcataria moluccana) industry becomes one of the raw materials in the manufactured of wood pellets, because of its potency. However F. moluccana pellets posses low density and calorific value. To improve its properties, a materials mixing with coconut shell parcticles was conducted. This study used material from the waste of sengon (F. moluccana) sawdust and the waste of coconut (Cocos nucifera). Particles from those materials were made on 3 sizes which are 20-40 mesh, 40-60 mesh, and 60-80 mesh. 25%, 50%, and 75% of coconut shell were added into sengon sawdust, while woode pellets with no additions were used as a control. Pellets are made using single-pelletizer at room temperature with a pressure of 100 kg/cm2. The research results showed if the different material combination (sengon and coconut shell) gave significant effect to physical properties and chemical content of wood pellets. Higher percentage of coconut shell gives higher compressive strength, fixed carbon content, total of carbon, and calorific value, while volatile matter, ash content, N, S, and H content showed lower value. The best pellet was resulted from combination between coconut shell addition 50% and nesh size 60 – 80 which posses quite low ash content (0.79%) and high calorific value (5129.07 Kal/g), and high compression strength (444.75 N). This result has qualified the standard of SNI 8021:2014.